2010
DOI: 10.1097/smj.0b013e3181cf373f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Eradication on Insulin Resistance, Serum Lipids and Low-Grade Inflammation

Abstract: This study showed beneficial effects of HP eradication on insulin resistance, atherogenic lipid abnormalities and low-grade inflammation. The results suggest that HP eradication may prevent coronary artery disease and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
6
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 33 publications
5
98
6
6
Order By: Relevance
“…It has also been reported that H.pylori infection plays a role in the regulation of leptin and ghrelin (Francois et al, 2011), two hormones involved in energy homeostasis where their interaction affects obesity, insulin sensitivity and glucose homeostasis (Sun et al, 2006;Williams and Mobarhan, 2003). Furthermore, H.pylori eradication seems to have beneficial effects on insulin resistance, lipid abnormalities and low-grade inflammation (Gen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that H.pylori infection plays a role in the regulation of leptin and ghrelin (Francois et al, 2011), two hormones involved in energy homeostasis where their interaction affects obesity, insulin sensitivity and glucose homeostasis (Sun et al, 2006;Williams and Mobarhan, 2003). Furthermore, H.pylori eradication seems to have beneficial effects on insulin resistance, lipid abnormalities and low-grade inflammation (Gen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The Maastricht IV consensus report declares that H. pylori eradication does not cause or worsen obesity and related illnesses 9. Recent studies showed the relationship between H. pylori and insulin resistance or diabetes 10. Accordingly, a favorable effect of H. pylori eradication on insulin resistance was also documented in some studies 11 . However, this relationship is not well defined yet due to some pitfalls in those studies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that six weeks after the end of eradication therapy, the mean fasting insulin, homeostasis model assessment-estimated insulin resistance (HOMA-IR), triglycerides (TG), light density lipoprotein C (LDL-C), and C-reactive peptide (CRP) levels in patients with successful eradication were significantly decreased from the pretreatment levels and high density lipoprotein C (HDL-C) level was significantly increased from the pretreatment levels. The mean fasting insulin, HOMA-IR, total cholesterol (TC), TG, LDL-C, CRP levels and HDL-C levels in patients with unsuccessful eradication were not significantly changed from pretreatment levels [20]. Other studies also showed positive lipid profile changes and inflammatory marker decrease [21].…”
Section: Metabolic Changes In Hp With T2dmmentioning
confidence: 70%